Implementasi Strategi Multiple Intelligences pada Pembelajaran Bahasa Inggris (Studi Kasus di SD Inklusi Semai Jepara) - Santi Andriyani (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2017)
Abstract: This study is aimed at: (1) describing the importance of multiple intelligences strategy in English learning and (2) describing the implementation of multiple intelligences strategy in English learning at SD Inklusi Semai Jepara. The writer uses Case Study method to describe deeply the implementation of multiple intelligences strategy in English learning at SD Inklusi Semai Jepara. Besides, the writer tries to find out the phenomenon in implementing of multiple intelligences strategy in English learning at SD Inklusi Semai Jepara.The findings of this study are: (1) The implementation of the MI method in SD Inklusi Semai Jepara has been starting since 2011; (2) the strategies that usually used in English learning are identification, clasification, song, games, simulation, and role play; (3)The contents of the lesson plan made by English teachers are identity, eksploration, elaboration, confirmation, MI strategy, and authentic assesment; (4) the supporting factors in implementing of multiple intelligences strategy in English learning at SD Inklusi Semai Jepara are from teachers, students, and parents; (5)the inhibiting factor in implementing of MI strategy in English learning at SD Inklusi Semai Jepara is the limited time for teachers in preparing all of the class administrations. Keywords: Multiple intelligences strategies, English for young learner, Case study